2020
DOI: 10.1111/geoj.12371
|View full text |Cite
|
Sign up to set email alerts
|

Production without medicalisation: Risk practices and disease in Bangladesh aquaculture

Abstract: Disease burdens threaten future food production, particularly so in the case of aquaculture. Reducing disease burden needs to consider not only the incidence of disease but also the socio‐economic effects of changing farming practices. Employing a multi‐method approach to farms in SW Bangladesh, we argue that understanding disease risk practices are central to any attempt to reduce disease burdens and unsustainable treatments of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Following earlier ethnographies that described antibiotic practices, 34–37 more recent studies in diverse global settings have shown how antibiotic use practices are shaped by pressures in people’s lives and livelihoods: within primary care in South Africa 38 and China; 26 , 39 hospitals in South Africa and/or India; 40–43 and community settings in Bangladesh 44 , 45 and Mozambique. 46 Researchers have also considered the logics of antibiotic use in the livelihoods of poultry farmers in Guatemala 47 and India; 48 Bangladeshi shrimp and prawn farmers; 49 , 50 and dairy farmers in India. 51 …”
Section: Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Following earlier ethnographies that described antibiotic practices, 34–37 more recent studies in diverse global settings have shown how antibiotic use practices are shaped by pressures in people’s lives and livelihoods: within primary care in South Africa 38 and China; 26 , 39 hospitals in South Africa and/or India; 40–43 and community settings in Bangladesh 44 , 45 and Mozambique. 46 Researchers have also considered the logics of antibiotic use in the livelihoods of poultry farmers in Guatemala 47 and India; 48 Bangladeshi shrimp and prawn farmers; 49 , 50 and dairy farmers in India. 51 …”
Section: Practicesmentioning
confidence: 99%
“… 38 Elsewhere, researchers revealed how a stewardship intervention targeting Bangladeshi aquaculturalists inadvertently caused their reliance on antibiotics to increase by ignoring risk profiles associated with local economic and ecological conditions, such as flooding. 50 They developed the concept of ‘risk-practices’ to help identify disease reduction opportunities and to avoid the pitfall of a one-size-fits-all response—based on the norms of food production in the Global North—when addressing antibiotic use. 50 …”
Section: Practicesmentioning
confidence: 99%
See 3 more Smart Citations